Beyond Likes: Social Media's Impact on Tourists' Festival Revisiting Intentions - Utami, Heryanti; Purnawan, Julius; Choirida; Amiruddin, Ja'far; Novitasari, Dewiana (IJOSMAS, 2024)
This study explores the interplay of social media, website quality, festival satisfaction, and festival revisiting intention in the context of tourism in Indonesia. Data were gathered from samples of 253 tourists at Festival Kebudayaan Yogyakarta (FKY) in Yogyakarta, Indonesia and analyzed using partial least square structural equation modelling (PLS-SEM) with the aid of SmartPLS (4.0). The research investigates the relationships between these variables to provide valuable insights for destination marketers and event organizers. The findings reveal that social media and website quality positively influence festival satisfaction, which in turn impacts tourists' intentions to revisit the festival. These results underscore the significance of leveraging social media and ensuring high website quality to enhance festival experiences and encourage repeat visitation. The implications of these findings extend to the broader tourism industry, offering valuable guidance for promoting sustainable and engaging cultural events in Indonesia and potentially in other similar contexts.